Soil phosphorus dynamics following land application of unsaturated and partially saturated red mud and water treatment residuals. (15th October 2019) - Brennan, R.B.; Murnane, J.G.; Sharpley, A.N.; Herron, S.; Brye, K.R.; Simmons, T.
Abstract: The secondary use of P-sorbing industrial by-products as a fertilizer or soil conditioner is gaining increased attention, particularly in light of diminishing reserves of rock phosphate traditionally used to manufacture P fertilizer. This study examined applications of red mud (RM) and water treatment residuals (WTR) at two levels of P saturation (i.e. 'as received' and partially saturated) in a soil incubation and runoff plot study. When incubated with soils ranging in texture and initial P concentration, P-sorbing residuals that were less enriched with P decreased water-extractable soil P (WEP) concentration to a greater extent than more P saturated residuals. In contrast to WTR treatments, not all of the RM applications decreased soil WEP concentrations below those of the control soils. The runoff study investigated soil P dynamics when partially P-saturated RM and WTR's were surface applied to grass plots at 2 t ha −1 on Day 0, followed by three rainfall simulations (7 cm h −1 for 30 min, Days 2, 7 and 28) and at 3 t ha −1 on Day 70 followed by two more rainfall simulations (Days 77 and 96). Application of residuals at these rates did not significantly increase dissolved reactive P (DRP) in runoff compared with unamended controls during the study. Forage cuttings taken 90 days after the first rainfall simulation indicated that nutrient uptake was not compromised by the application of the residuals. Overall results indicate that WTRs may be a more suitable soil amendment than RM residuals given their greater ability to reduce soil WEP across a range of soils without simultaneously increasing Mehlich-3 extractable soil P concentrations above the upper threshold limit (150 mg P kg −1 ), and their minimal impact on plant nutrient uptake. Highlights: P-sorbing residuals were examined in a soils incubation and plot runoff study . Water treatment residuals may be more suitable than red mud to reduce soil WEP. Use of water treatment residuals did not increase soils M3-P above 150 mg P kg −1 . Use of residuals as fertilizer had minimal adverse effects on forage uptake.